1996
DOI: 10.2741/a107
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electrosigmoidography Study of the myoelectric activity of sigmoid colon by surface electrodes

Abstract: The purpose of this study was to determine the feasibilty of performing transcutaneous electrosigmoidography (TC-ESG). The study involved 19 healthy volunteers (11 men, 8 women; mean age 38.2 +/- 14.8 years). To validate the results of TC-ESG, the latter was performed simultaneously with intra-sigmoid ESG. TC-ESG was done also in five patients who underwent sigmoidectomy. The optimal position of the electrodes was determined after several trials. Two electrodes (Beckman) were applied, each 2-3 cm away from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 15 publications
3
48
1
Order By: Relevance
“…The waves were recorded either transluminally or percutaneously (5,18,19,23). Wave abnormalities were detected in the electrogram of the aforementioned organs when they were diseased (5,6,12,13,16,17,24,25) .…”
Section: Introductionmentioning
confidence: 99%
“…The waves were recorded either transluminally or percutaneously (5,18,19,23). Wave abnormalities were detected in the electrogram of the aforementioned organs when they were diseased (5,6,12,13,16,17,24,25) .…”
Section: Introductionmentioning
confidence: 99%
“…The technique was described previously [14] and will be men tioned here briefly. The subject was asked to abstain from urination for at least 4 h prior to testing.…”
Section: Technique Of Transcutaneous Electrovesicographymentioning
confidence: 99%
“…Like the other smooth muscles in the gut [ 1 -10] and cavernous tis sue [11,12], it possesses an electric as well as mechanical activity [13]. Recent studies [13,14] have shown that the electric waves or pacesetter potentials (PPs) evoked by the vesical detrusor were triphasic with a small positive, a large negative and another small positive deflection. The PPs in each subject showed the same frequency and regu lar rhythm at each repetition of the test.…”
mentioning
confidence: 99%
See 2 more Smart Citations